2021
DOI: 10.1108/medar-09-2019-0549
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enterprise risk management on financial performance and firm value: the role of environmental, social and governance performance

Abstract: Purpose This study aims to examine the effect of enterprise risk management (ERM) on financial performance and firm value, as well as the moderating role of environmental, social and governance (ESG) performance. Design/methodology/approach The samples in this study are listed companies in the ASEAN 5 (Indonesia, Malaysia, Philippines, Singapore and Thailand) during the years 2014–2018, with total observations of 680 firm-years. Fixed effect panel data regressions were used to test the hypotheses. The data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
8
36
0
4
Order By: Relevance
“…To test whether the ESGRISK-SGR relationship between environmentally sensitive and non-sensitive industries is different, we divide the whole company sample into environmentally sensitive and non-environmentally sensitive industries. The business activities of environmentally sensitive industry firms (such as oil, gas, paper, metal manufacturing, and chemical) have a direct impact on ESG issues [66][67][68][69] and are often perceived as polluting sectors that pose higher environmental risks [31,32].…”
Section: Effect Of Esgrisk On Sgr: Environmentally Sensitive Vs Non-sensitive Industriesmentioning
confidence: 99%
“…To test whether the ESGRISK-SGR relationship between environmentally sensitive and non-sensitive industries is different, we divide the whole company sample into environmentally sensitive and non-environmentally sensitive industries. The business activities of environmentally sensitive industry firms (such as oil, gas, paper, metal manufacturing, and chemical) have a direct impact on ESG issues [66][67][68][69] and are often perceived as polluting sectors that pose higher environmental risks [31,32].…”
Section: Effect Of Esgrisk On Sgr: Environmentally Sensitive Vs Non-sensitive Industriesmentioning
confidence: 99%
“…Furthermore, for the influence of the second control variable, namely leverage where the results of statistical calculations were known that the leverage variable had a negative and significant effect on return on assets of -0.513 while the leverage variable on the market book ratio has a negative and insignificant effect of -0.318 while the leverage variable on Tobisn q has a negative and insignificant effect on positive and not significant at 0.059. This indicates that investors need a long time to respond to information related to economic, social and environmental issues in sustainability reporting (Chairani and Siregar, 2021;García et al, 2018).…”
Section: Results and Analysismentioning
confidence: 99%
“…According to signal theory, ESG practices can signal compliance with the norms of sustainable business behavior (Belkaoui, 1976). ESG practices also pay attention to various environmental, social, and governance issues to address areas characterizing sustainable, responsible, and ethical investment (Chairani & Siregar, 2021). When an entity shows behavior that is relevant to the values in society, the entity will get a good assessment from the public (Pham & Tran, 2020).…”
Section: Environmental Social and Governance (Esg) And Foreign Invest...mentioning
confidence: 99%
“…Therefore, investors tend to be more attracted to companies with better ESG performance. Chairani and Siregar (2021) documented that ESG practices in a company can be a strong attraction for foreign investment. Further, research conducted before (Liu et al, 2021) at the level of foreign direct investment in 44 countries revealed that high ESG scores reflect important intangible assets and help the internationalization of companies by promising good governance and management systems and sustainable business prospects.…”
Section: Environmental Social and Governance (Esg) And Foreign Invest...mentioning
confidence: 99%